تفسير قوله تعالى "وما أرسلنا من قبلك من رسول ولا نبي إلا إذا تمنى ألقى الشيطان في أمنيته" "الحج 52" والآيتان بعدها: تفسيراً تحليلياً - العنزي، علي بن جريد بن هلال (الجامعة الإسلامية بالمدينة المنورة, 2019)
هذه الدراسة في تفسير قوله تعالى: (وَمَا أَرْسَلْنَا مِنْ قَبْلِكَ مِنْ رَسُولٍ وَلَا نَبِيٍّ إِلَّا إِذَا تَمَنَّى أَلْقَى الشَّيْطَانُ فِي أُمْنِيَّتِهِ) ]الحج: 52[ والآيتان بعدها، تفسيراً تحليلياً. تناولت الدراسة مسألة نزول سورة الحج هل كان بمكة أم كان بالمدينة؟ ثم الآيات التي دار الحديث فيها وكونها نزلت بمكة-شرفها الله-. في الدراسة جمع لأقوال المفسرين وموازنة بينها وترجيح مع ذكر الحجة غالبا. وفيها ذكر للطائف بلاغية، ونكت عربية. كما ألقي الضوء على قصة الغرانيق ومدى صحتها، ومن ضعفها؟ وما الحجة في تضعيفها؟ ومناقشة من قال بقوتها. تناول الباحث تعريف النبي والرسول، وهل هناك فرق بينها؟ كان في ثنايا الدراسة ذكر جمل من الاستنباطات العلمية.
This study focused on the interpretation of the verse: {And We did not send before you any messenger or prophet except that when he spoke [or recited], Satan threw into it [some misunderstanding], and the two verses after it, followed by an analytical interpretation. The study dealt with the issue of Surat Al-Hajj revelation, was it revealed in Makkah or in Madinah? Then the above discussed verses, and the fact that they were revealed in Makkah. This study, included a collection of the interpreters' sayings, comparing them, validating and mentioning the evidence in most cases. It also included rhetorical witticisms and Arabic anecdote. As it also shed light on the Garaaniq story, its authenticity and weakness? What is the evident regarding its weakness? And discussing the thoughts of those who support it. The researcher dealt with the definition of a Messenger and a Prophet, and the difference between them? The study also included a mention of a number of scientific deductions.
Keywords: القرآن الكريم -- سورة الحج -- تفسير القرآن -- العقيدة الإسلامية